Monetary Interventions and the Rise of Non-Bank Lenders - Gianluca Cafiso; Giulia Rivolta (Center for Economic Studies and ifo Institute (CESifo), 2022)
The amount of assets managed by non-bank lenders has increased significantly over the last decades. Our research aims to clarify whether such an increase has had any impact on the effectiveness of monetary policy. To this end, we consider several credit aggregates granted from bank and non-bank institutions for different scopes and developments in the US economy. Our analysis is based on the estimation of a large Bayesian VAR. The results suggest that the rise of non-bank lenders has reduced and altered the monetary policy transmission mechanism.
Keywords: E44; E51; G20; G21; C11; 330; bank loans; non-bank loans; monetary interventions; Bayesian VAR